Genomic Analysis of Storage Protein Deficiency in Genetically Related Lines of Common Bean (Phaseolus vulgaris) - Pandurangan, Sudhakar; Diapari, Marwan; Yin, Fuqiang; Munholland, Seth; Perry, Gregory E.; Chapman, B. Patrick; Huang, Shangzhi; Sparvoli, Francesca; Bollini, Roberto; Crosby, William L.; Pauls, Karl P.; Marsolais, Frédéric (Frontiers in Plant Science, 2016)
A series of genetically related lines of common bean (Phaseolus vulgaris L.) integrate a progressive deficiency in major storage proteins, the 7S globulin phaseolin and lectins. SARC1 integrates a lectin-like protein, arcelin-1 from a wild common bean accession. SMARC1N-PN1 is deficient in major lectins, including erythroagglutinating phytohemagglutinin (PHA-E) but not α-amylase inhibitor, and incorporates also a deficiency in phaseolin. SMARC1-PN1 is intermediate and shares the phaseolin deficiency. Sanilac is the parental background. To understand the genomic basis for variations in protein profiles previously determined by proteomics, the genotypes were submitted to short-fragment genome sequencing using an Illumina HiSeq 2000/2500 platform. Reads were aligned to reference sequences and subjected to de novo assembly. The results of the analyses identified polymorphisms responsible for the lack of specific storage proteins, as well as those associated with large differences in storage protein expression. SMARC1N-PN1 lacks the lectin genes pha-E and lec4-B17, and has the pseudogene pdlec1 in place of the functional pha-L gene. While the α-phaseolin gene appears absent, an approximately 20-fold decrease in β-phaseolin accumulation is associated with a single nucleotide polymorphism converting a G-box to an ACGT motif in the proximal promoter. Among residual lectins compensating for storage protein deficiency, mannose lectin FRIL and α-amylase inhibitor 1 genes are uniquely present in SMARC1N-PN1. An approximately 50-fold increase in α-amylase inhibitor like protein accumulation is associated with multiple polymorphisms introducing up to eight potential positive cis-regulatory elements in the proximal promoter specific to SMARC1N-PN1. An approximately 7-fold increase in accumulation of 11S globulin legumin is not associated with variation in proximal promoter sequence, suggesting that the identity of individual proteins involved in proteome rebalancing might also be determined at the translational level.